2017
DOI: 10.12659/msm.900343
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Single-Balloon Versus Double-Balloon Enteroscopy: A Single-Center Retrospective Analysis

Abstract: BackgroundSingle-balloon endoscopy (SBE) has been introduced as a simplified endoscopy technique after the promotion of double-balloon endoscopy (DBE). The difference in clinical performance between DBE and SBE is still not very clear. In this study, we aimed to compare the efficacy and safety between these 2 endoscopic procedures.Material/MethodsA total of 173 patients with suspected small bowel disease were enrolled into this study from January 2007 to December 2011. All cases were divided into DBE or SBE gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“… Forest plot showing the diagnostic yields of all studies included in the meta-analysis and the pooled diagnostic yields calculated by random and fixed effects models. 1 , 9 , 10 , 16 , 17 , 22 - 22 , 25 , 30 , 32 , 40 - 40 , 42 , 61 - 61 …”
Section: Figmentioning
confidence: 99%
“… Forest plot showing the diagnostic yields of all studies included in the meta-analysis and the pooled diagnostic yields calculated by random and fixed effects models. 1 , 9 , 10 , 16 , 17 , 22 - 22 , 25 , 30 , 32 , 40 - 40 , 42 , 61 - 61 …”
Section: Figmentioning
confidence: 99%
“…7 After Enteroscopy, there was not any major complication and just some degrees of abdominal pain reported in 4.8% of cases which is concordance with the study of Ramchandani et al 12 This low rate of complications have confirmed in more recent studies which prove the safety of balloon enteroscopy not only as a diagnostic method but also for therapeutic interventions. 13,14 The results of current work indicate that there is a significant relationship between chronic renal failure (CRF) and Angiectasia (P=0.03). This relation is a well-known complication of CRF 15 and explained by accelerated early vascular ageing process mediated by medial vascular calcification.…”
Section: Discussionmentioning
confidence: 83%
“…A few studies analysing the indications, efficacy, outcomes, and safety of enteroscopy procedures have been carried out in various countries. The efficacy of SBE was also compared with that of double balloon enteroscopy in several retrospective studies and meta-analyses[ 16 - 20 ]. Moreels et al [ 21 ] conducted a case series in 2016 evaluating the therapeutic actions of SBE using a new prototype and highlighting its benefits.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been previously reported that the adverse effects seen in SBE procedures were comparable to those seen in DBE procedures, with both being marked as safe according to a single-centre retrospective analysis. However, the study accounted for a performance bias as all the procedures were carried out by a single endoscopist, who was trained in the procedure[ 20 ]. One study on the usage of emergency SBE concluded that the incidence of adverse effects was lower when general anaesthesia was used as compared to when it was performed under conscious sedation[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation